Reframing Turnover Intention: Exploring the Influence of Career Identity, Career Success, and Social Support Through Work Engagement - Wulandari, Fransisca Eka; Tanuwijaya, Justine; Noor, Noerzanah Mat (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study investigates the influence of career identity, career success, and social support on turnover intention, with work engagement serving as a mediating variable among PT employees. Bank Mandiri (Persero) Tbk in Jakarta. The study aims to analyze the direct and indirect relationships among these variables and to examine the mediating role of work engagement in reducing employees’ intention to leave the organization. The population consisted of all employees working at the head office, branch offices, and regional offices in Jakarta. Using stratified proportional sampling, 277 respondents were selected. The findings reveal that career identity, career success, and social support significantly enhance work engagement. In addition, work engagement has a significant negative effect on turnover intention and partially mediates the relationship between the independent variables and turnover intention. Theoretically, this study enriches the literature on turnover intention by integrating career-related and social contextual factors within a mediation framework. The study is limited to a single organization and geographic area. Future research should involve multiple organizations, diverse sectors, and longitudinal approaches to improve generalizability and causal inference.